Rise and Fall of the Spanish Colonial Dream in Africa: Former Civilian Colonists’ Emotions and their Gendered Experiences Facing African Voices - Aixelà-Cabré, Yolanda; Justus Liebig University Giessen (My University, 2021)
This chapter approaches the Spanish colonization in Morocco and Equatorial Guinea through the experiences and emotions of the Spaniards who migrated to these countries. Emotions of colonial dreams emerged in the narratives of Spanish informants in search of an economic paradise that, with colonial independences, changed into bitterness and imperial nostalgia. These Spanish narratives are confronted with African voices to observe what reality paradise had for subaltern groups. The result of the comparison was shocking because some African voices remembered the colonial past with nostalgia. That point was interpreted as a powerful criticism to their unequal current political systems.
Keywords: Spanish colonial dream; gendered experiences; nostalgia; Spanish Protectorate of Morocco; Spanish Guinea; ddc:300